2015
DOI: 10.1186/s12885-015-1177-1
|View full text |Cite
|
Sign up to set email alerts
|

The leukemia inhibitory factor (LIF) and p21 mediate the TGFβ tumor suppressive effects in human cutaneous melanoma

Abstract: BackgroundCutaneous melanoma is the most lethal skin cancer and its incidence in developed countries has dramatically increased over the past decades. Localized tumors are easily treated by surgery, but advanced melanomas lack efficient treatment and are associated with very poor outcomes. Thus, understanding the processes underlying melanoma development and progression is critical. The Transforming Growth Factor beta (TGFβ) acts as a potent tumor suppressor in human melanoma, by inhibiting cell growth and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…We cannot exclude the possibility that the decreased levels of STAT3 were mediated by the degradation of NPM-ALK induced by TFP. Additionally, the cell cycle regulatory proteins p21, p27, and CDK2 are directly regulated by STAT3 [26][27][28]. Our data demonstrated that the cell cycle arrest induced by TFP was related to the degradation of STAT3.…”
Section: Discussionmentioning
confidence: 61%
“…We cannot exclude the possibility that the decreased levels of STAT3 were mediated by the degradation of NPM-ALK induced by TFP. Additionally, the cell cycle regulatory proteins p21, p27, and CDK2 are directly regulated by STAT3 [26][27][28]. Our data demonstrated that the cell cycle arrest induced by TFP was related to the degradation of STAT3.…”
Section: Discussionmentioning
confidence: 61%
“…The dissection of the molecular mechanisms underlying various functions of NeuroD2 was done through documentation of its targets. NeuroD2 was found to upregulate transcript levels of IL‐24, BMP2 and LIF . Interestingly, previous reports of these factors show cancer specific growth suppressing and apoptosis inducing properties.…”
Section: Discussionmentioning
confidence: 80%
“…NeuroD2 was found to upregulate transcript levels of IL-24, BMP2 and LIF. [24][25][26] Interestingly, previous reports of these factors show cancer specific growth suppressing and apoptosis inducing properties. NeuroD2 also suppresses the expression of proinflammatory cytokines such as CXCL8 and IL6 whereas increases the level of others such as CXCL5 and IL1B.…”
Section: Cancer Genetics and Epigeneticsmentioning
confidence: 97%
“…The TGFβ/EMT signaling pathway serves a crucial role in mediating tumor suppressive effects in human cutaneous melanoma (20). TGFβ-mediated formation of retinoblastoma protein-E2F complexes has been demonstrated to be involved in the proliferation and invasion of human myeloid leukemia cells (29).…”
Section: Discussionmentioning
confidence: 99%